Analisis Peran Manajemen Risiko dalam Perpajakan: Perspektif dari Studi Literatur - Ade Puspita, Reni Suwandi; Wahono, Puji; Pahala, Indra (Fakultas Ekonomi dan Bisnis dan LPPM Universitas Negeri Jakarta, 2024)
This research aims to explore the role of risk management in the tax context through in-depth literature study analysis. In an increasingly complex and dynamic tax environment, risk management plays an important role in identifying, analyzing and managing risks related to tax compliance and fiscal management. Through a review of various literature, this research presents the main approaches in tax risk management, including risk identification techniques, risk assessment, and mitigation strategies implemented by tax authorities and taxpayers. Research findings show that tax risk management is not only important for mitigating potential financial losses and maintaining the law, but also for improving the efficiency of tax administration and optimizing tax strategies. In addition, this research reveals various challenges faced in implementing risk management and provides recommendations for further research which includes empirical studies and international comparisons to deepen understanding of best practices in risk management taxation. The conclusion of this research emphasizes the need for a more comprehensive integrated risk management strategy to increase the effectiveness of the tax system.